Pulmonary artery intramural hematoma: Unusual complication of aortic dissection - Valle, Felipe Homem; Gib, Marcelo; Torres, Felipe (Clinical and Biomedical Research, 2015)
A 56 year-old patient presented to the emergency room with chest pain and 26mmHg blood pressure gap between right arm and left lower limb. The hypothesis of aortic dissection was evaluated through chest CT, which showed a Stanford type A aortic dissection with extension through the pulmonary artery and the presence of an intramural hematoma extending along the main and right pulmonary arteries.